Transition énergétique et durabilité de l’agriculture : les limites et paradoxes du développement de la méthanisation agricole. Etude comparée en Bretagne et Grand-Est - Nadège Garambois; Isaline Reguer; Nathan Pirard; Floris Schruijer (Territoire en Mouvement)
In recent years, French energy policy has been increasingly oriented towards renewable energies, creating a new demand for French agriculture, which goes beyond its mission of producing agricultural products to include energy (electricity, gas, heat), particularly through the development of agricultural methanisation. This research, based on the study of the recent development of agricultural methanisation in two small agricultural regions of Bretagne and Grand-Est, highlights the limits and paradoxes of the deployment of this conception of the energy transition in agriculture: high investments that lead to inequality of access to these projects, reinforcement of existing social inequalities, and incomes that are highly dependent on subsidised energy rates. It invites to question the compatibility of this movement with the perspective of setting up a more sustainable and equitable agriculture.